Country virtual learning exchange workshop series: Insights from Kyrgyzstan - Ibraeva, Gulnara; Ablezova, Mehrigiul; Danshina, Anastasiia; Elias, Marlene (2024)
The webinar commenced with an overview of the project’s background including the gender analysis methodology. Key findings from the gender analysis were presented, shedding light on challenges such as lack of information, gender disparities in land rights, and conservative shifts in communities. Moreover, the webinar provided insights into the pilot design and implementation, including legal counselling, trainings on financial literacy, social media marketing, and family harmony, as well as study tours. Throughout the session, speakers offered recommendations for addressing gender inequalities and promoting women’s empowerment in land ownership, with an emphasis on replicating and scaling up GTAs in other contexts.